(3WjHI GdfTQ aj GdbQGAGJ GdYTQs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,J (B833 (3g` s
(3ChdgG (B:s
(3JUfja GdEeGe GdYGde GdYdGeI CHh GdNjQ eMeO TeS GdOjf SeY GdMOjK ef GdTjN GdYdGeI UdGM GdOjf eMeO Hf EHQGgjebGd eMeO GHf GdLRQi jGPG GdLdGd GQMeg hGSJQ hGZaQ s
(3BNQgG (B:s
(3QeGjI HTQWgG GdeYJHQ hbGdg eMeO Hf GdLRQi jQMeg HaVdg GdQMeGf aXfg ef LhOg GdZaQGf s
(3GdfSNI HgG MhGTs
(3jdjgG (B" (3GdhGajI ai TQM GdcGajI (B"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B45 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B291s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1118s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs